2002
DOI: 10.1016/s1387-7003(02)00585-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substitution of a thioether donor by a phosphine donor in thiacrown complexes of iron

Abstract: Michael J. (2002) The effect of substitution of a thioether donor by a phosphine donor in thiacrown complexes of iron. AbstractElectrospray mass spectrometry and thermogravimetric analysis reveals that bis(1-phenyl-1phospha-4,7-dithiacyclononane)iron(II) is more susceptible to ethene loss than bis(1,4,7trithiacyclononane)iron(II). This is in accord with X-ray crystallographic studies, which show that the C-S bonds are longer in the former complex suggesting an increased population of the C-S   -acceptor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Indeed, several previous reports involving facially spanning 1,4,7-trithia cyclononane (9S 3 ) complexes [M(9S 3 ) 2 ] + (M = Tc, Re, Ru, Os) provide evidence for the susceptibility of these systems for ethene loss. 16 While the incorporation of a phosphine center within the macrocyclic framework (e.g., 9PS 2 ligands) improved the kinetic inertness of [Mo(9PS 2 )(CO) 3 ] + in comparison with [Mo(9S 3 )(CO) 3 ] + , the reverse has been found to be true in a comparative study of [Fe(9S 3 ) 2 ] 2+ and [Fe(9PS 2 ) 2 ] 2+ . 16 In this context, results from our current studies have demonstrated that the compact PS 2 ligand system possesses topology for facial tridentate coordination with Tc(CO) 3 + /Re(CO) 3 + cores, thereby producing five-membered [M(CO) 3 (PS 2 )] + (M = Tc/Re) compounds that are both kinetically robust and in vivo stable.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several previous reports involving facially spanning 1,4,7-trithia cyclononane (9S 3 ) complexes [M(9S 3 ) 2 ] + (M = Tc, Re, Ru, Os) provide evidence for the susceptibility of these systems for ethene loss. 16 While the incorporation of a phosphine center within the macrocyclic framework (e.g., 9PS 2 ligands) improved the kinetic inertness of [Mo(9PS 2 )(CO) 3 ] + in comparison with [Mo(9S 3 )(CO) 3 ] + , the reverse has been found to be true in a comparative study of [Fe(9S 3 ) 2 ] 2+ and [Fe(9PS 2 ) 2 ] 2+ . 16 In this context, results from our current studies have demonstrated that the compact PS 2 ligand system possesses topology for facial tridentate coordination with Tc(CO) 3 + /Re(CO) 3 + cores, thereby producing five-membered [M(CO) 3 (PS 2 )] + (M = Tc/Re) compounds that are both kinetically robust and in vivo stable.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that unbound benzyldivinylphosphine acted as a base to abstract a proton from the acidic NH 2 groups thus enabling attack of the liberated nitrogen lone pair at a coordinated benzyldivinylphosphine [289]. Complete conversion to the macrocyclic species was achieved after removal of the original reaction solvent, dissolution of the residues in THF and reaction with potassium tert- spectroscopy and elemental analysis [99], although the nickel(II) and iron(II) complexes were subsequently characterised with X-ray crystallography [304,305].…”
Section: Syntheses and Properties Of Metal Complexesmentioning
confidence: 99%
“…Crystal structure of 7-phenyl-1,4,7-dithiaphosphonane 7-sulfide[303] Iron(II) The structure of [Fe([9]aneP(Ph)S 2 ) 2 ](BF 4 ) 2 is pseudo octahedral with the phosphine donors trans(Figure 113)[304]. The Fe-S distances (2.2445(7) Å and 2.2516(7) Å) and the Fe-P distance of 2.2244(7) Å was significantly shorter than both the Fe-S distances and Cambridge Crystallographic Database average for iron-phosphine bonds (2.25 Å)[304].…”
mentioning
confidence: 99%
See 2 more Smart Citations